Enhancing resilience with natural growth targeting - Athanasios Orphanides (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
Despite a number of helpful changes, including the adoption of an inflation target, the Fed's monetary policy strategy proved insufficiently resilient in recent years. While the Fed eased policy appropriately during the pandemic, it fell behind the curve during the post-pandemic recovery. During 2021, the Fed kept easing policy while the inflation outlook was deteriorating and the economy was growing considerably faster than the economy's natural growth rate-the sum of the Fed's 2% inflation goal and the growth rate of potential output. The resilience of the Fed's monetary policy strategy could be enhanced, and such errors be avoided with guidance from a simple natural growth targeting rule that prescribes that the federal funds rate during each quarter be raised (cut) when projected nominal income growth exceeds (falls short) of the economy's natural growth rate. An illustration with real-time data and forecasts since the early 1990s shows that Fed policy has not persistently deviated from this simple rule with the notable exception of the period coinciding with the Fed's post-pandemic policy error.
Keywords: E32; E52; E58; E61; 330; Federal Reserve; monetary policy strategy; discretion; simple rules; real-time data